Isolation and characterization of polyethylene-biodegrading mycromycetes - Méndez, Carmen R. (2006)
The polyethylene biodegradation by microorganisms is a solution for the reduction of the plastics pollution. Isolation and characterization of the fungi capable to degrade the polyethylene are reported, as well as the conditions of pH and temperature in which they showed the higher activity. Fungi were isolated from polyethylene products obtained of sanitary landfill; the identification was realized in base to growth in petri plate and the technique of microculture in sheet. Biodegradative activity was determined with the Kavelman and Kendrick technique, for temperatures between 20 and 30 °C and to pH 4,5 – 8,0. Twenty strains of micromicete were isolated and identified. Five strain (25%) shown polyethylene biodegradative capacity to 20 °C, and pH 6,5. Six strain (30%) showed activity biodegradative to 30 °C, and pH 6,5. In both cases, Aspergillus flavus was the strain with greater performance.